Cultural resources, academic self-concept, and achievement of chemistry students in senior secondary schools of Calabar Municipality, Cross River State, Nigeria - Nja, Cecilia Obi; Ukwetang, John Okpa; Orim, Richard Ekonesi; Neji, Hope Amba; Edu, Grace Onya; Ukah, Julius Ukah; Olofu, Martin Afen (Frontiers in Education, 2022)
This paper investigated cultural resources, academic self-concept, and achievement of chemistry students in senior secondary school two in Calabar Municipality, Cross River State. Nigeria. Research questions and hypotheses were formulated to direct the study. Quasi, experimental factorial design was used in this study. A sample size of 90 senior secondary chemistry students was used. Two instruments were used: Academic Self-concept Questionnaire (ASCQ) and Chemistry Achievement Test (CAT). The reliability of (ASCQ) was done using Cronbach Alpha and it was 0.80 while the reliability of (CAT) was done using Kuder Richardson formula 20 and had a coefficient of 0.79. The results obtained were analysed using a dependent t-test and analysis of variance ANCOVA. Analysis of data showed that students’ academic self-concept increased after using cultural resources and the experimental group gain more than the control. The implication of this study is that cultural resources made learning chemical concepts easy to comprehend as they were materials learners are familiar with. It was recommended among others that teachers use cultural resources in teaching chemistry. Key words; Cultural resources, self-concept, achievement, students, and ethno chemistry.